Comparative analysis: Surrogacy regulation in India and global perspectives (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This research paper examines the complex regulatory environment surrounding surrogacy in India, investigating its historical development and the intricate interplay of legal, ethical, and cultural factors. The paper examines the regulatory reforms that ensued after India became a prominent international hub for commercial surrogacy, with a specific emphasis on the intricate provisions of the Surrogacy (Regulation) Act, 2021. It emphasizes the impact of the act and addresses any limitations that were previously present. This study investigates the constitutional and legal ramifications that arise from the criteria for eligibility, with a particular focus on the effects on the infant, surrogate mothers, and intended parents. With the assistance of a global comparative analysis, this paper provides a nuanced perspective on surrogacy laws in Ukraine, the United States, and the United Kingdom, among others. These three jurisdictions were selected due to the fact that their surrogacy legislations regulate the industry to varying degrees: Ukraine regulates commercial surrogacy, the United States has state-made legislation, and the United Kingdom's legislation is very similar to that of India. The core of the manuscript consists of ten recommendations that are specifically designed for the Indian context. These recommendations promote the following: comprehensive legislation, parental rights recognition, autonomy for surrogate mothers, and ethical guidelines. The aforementioned suggestions encompass public education initiatives, anti-discrimination protocols, and international surrogacy regulations. In conclusion, the paper proposes a legal structure that is congruent with the cultural heterogeneity of India, thereby cultivating an atmosphere for surrogacy arrangements that is ethical, inclusive, and transparent.